(untitled) (Bangladesh Journal of Neuroscience, 2015)
Purpose: To analyze the socio-demographic and electro-clinical data of Epilepsy patients presenting in the ‘Epilepsy Clinic’ of a referral hospital. Method: Epilepsy patients came to this weekly clinic after referral from this hospital OPD, other hospitals and from private practitioners. All the patients were enrolled from November, 2012 to December, 2015. Then clinical diagnosis was established by the chief investigator. Routine EEG was done. MRI was advised in appropriate cases. Finally the clinical findings and investigation reports were correlated. Results: Among 331 patients, 63% were male and 37% were female. 86% patients were in the younger age group (0- 29years). 75% patients were suffering from various forms of LRE, 19% from Generalized Epilepsy Syndrome, 2.7% were unclassified and 2.7% had pseudo-seizure. Total 224 EEG could be done. Among them 118 (52.7%) had different types of abnormalities. Among total 158 MRI, 120 (76%) were abnormal. 6.3% patients could not go to school, 3.3% left study and 12.7% patients remain unemployed due to the disease burden. Conclusion: This is a hospital based study. In this study LRE comprises 75% of total patients which is relatively higher than other reports. Males were predominating and younger people were affected more with epilepsy. Due to this disease various social problems were occurring regarding study and employment. This result demands community based larger study in our country. Bangladesh Journal of Neuroscience 2015; Vol. 31 (2): 83-93